(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The evolution of retail channels has significantly influenced consumer behaviour. This study examines consumer behavior and shopping experiences across online and offline mall-based retail channels. It identifies key trends shaping consumer preferences, including the convenience and accessibility of online platforms and the sensory engagement offered by physical stores. Online shopping behaviors are characterized by price sensitivity, reliance on reviews, and demand for personalization, while offline shopping emphasizes tactile interaction, experiential elements, and immediate product ownership. Comparative analysis reveals that online channels excel in product variety and cost-effectiveness, whereas offline channels thrive on trust and sensory evaluation. Both channels face unique challenges, such as building trust online and maintaining relevance offline. Hybrid models and omnichannel strategies, integrating technology like AI and AR, are highlighted as pivotal for meeting evolving consumer expectations. Additionally, sustainable practices and the transformation of retail spaces into lifestyle hubs emerge as crucial for future success. By addressing these dynamics, retailers can create seamless, engaging experiences that cater to diverse consumer needs, ensuring competitiveness in a rapidly changing retail landscape.